161k views
0 votes
Simplify


\ \textless \ br /\ \textgreater \ \sqrt[4]{16a^- 12}\ \textless \ br /\ \textgreater \ ​

​​

User Saray
by
5.9k points

1 Answer

6 votes

Answer:


\huge\boxed{\sqrt[4]{16a^(-12)}=2a^(-3)=(2)/(a^3)}

Explanation:


16=2^4\\\\a^(-12)=a^((-3)(4))=\left(a^(-3)\right)^4\qquad\text{used}\ (a^n)^m=a^(nm)\\\\\sqrt[4]{16a^(-12)}=\bigg(16a^(-12)\bigg)^(1)/(4)\qquad\text{used}\ a^(1)/(n)=\sqrt[n]{a}\\\\=\bigg(2^4(a^(-3))^4\bigg)^(1)/(4)\qquad\text{use}\ (ab)^n=a^nb^n\\\\=\bigg(2^4\bigg)^(1)/(4)\bigg[(a^(-3))^4\bigg]^(1)/(4)\qquad\text{use}\ (a^n)^m=a^(nm)\\\\=2^{(4)((1)/(4))}(a^(-3))^{(4)((1)/(4))}=2^1(a^(-3))^1=2a^(-3)\qquad\text{use}\ a^(-n)=(1)/(a^n)


=2\left((1)/(a^3)\right)=(2)/(a^3)

User Kou S Hal
by
6.4k points